MODEL KOMUNIKASI DAKWAH ADAPTIF PADA MASYARAKAT KONTEMPORER DENGAN INTENSITAS AKTIVITAS TINGGI - Anita Anita (Lembaga Sepercenter, 2026)
The phenomenon of time constraints among individuals with high activity intensity reveals a gap between spiritual needs and access to da’wah. Full-time workers, full-day students, and highly mobile urban communities often experience physical fatigue and psychological pressure that limit participation in conventional da’wah forums. These conditions require a more adaptive, contextual, and experience-oriented approach to da’wah communication.This study aims to formulate an Adaptive Da’wah Communication Model as a conceptual framework responsive to the realities of contemporary society characterized by high activity intensity. Employing a qualitative approach through library research and thematic-constructive analysis within the perspective of da’wah communication, data were derived from scholarly literature in the fields of da’wah, communication, digital media, and social transformation.The findings indicate that the Adaptive Da’wah Communication Model is structured upon six core elements: (1) the existential condition of mad’u, (2) activity-based segmentation, (3) psychological message adjustment, (4) micro-content utilization, (5) digital media transformation, and (6) on-demand accessibility. The model is operationalized through a six-stage cyclical process, ranging from identifying the condition of mad’u to evaluating audience responses.This model enables da’wah communication to remain relevant, flexible, and effective within time-constrained and high-pressure social environments. The study contributes theoretically to the development of a more contextual, adaptive, and responsive framework in da’wah communication studies.